THE INFLUENCE OF LEVEL CROSSINGS ON ECONOMIC GROWTH AND SOCIAL DYNAMICS IN CIREBON CITY - Novriani, Shinta; Hariani, Mira Lestira; Rohman, Fathur (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2023)
Cirebon City is one of the metropolitan areas stipulated in PP No. 26 of 2008 namely RTRWN as a National Activity Center (PKN) in developing metropolitan areas, especially in Ciayumajakuning area. The Cirebon City has become the center of economic growth, resulting in an increase in the flow of urbanization and in line with social dynamics that must be considered due to urban city activities. One of the impacts of urban cities is the increase in traffic density, causing a decrease in traffic performance. The purpose of this study is to determine the existing conditions of railroad level crossings in Cirebon City and see their impact on traffic performance, social dynamics and economic growth in Cirebon City. The research method used is a survey method, including traffic volume surveys, train frequency surveys, and calculating queue lengths and calculating delays. Based on the result of a survey on 8 roads in the Cirebon City with an average capacity of 3191 smp/hour, the degree of saturation is 0.5, the Level of Service value is C, which means the flow is stable, the speed can be controlled by traffic. However, if it is review based on an economic analysis related to the loss of community income due to level crossings if it is assumed that the average income of the people of Cirebon City is IDR 2.304.943.51 each individual experiences losses ranging from IDR 0 – IDR 768.314 for one month depending on the how long the individual experiences waiting time at a level crossing. If analyzed based on fuel consumption, each individual experiences a loss of IDR 0 – IDR 30.294 per month depending on the waiting time and the type of fuel used and if it is associated with the economic growth of Cirebon City, it is expected to increase the contribution of GRDP for each sector and respondents feel that level crossing are very important affect their travel interest.